ANALISIS MUSIK IRINGAN TARI JEPIN ROTAN KARYA MUHAMMAD YUSUF DAHYANI - Mandasari, Gesty; Ghozali, Imam; Silaban, Chiristianly Yeri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the uniqueness of vocal melodies in Jepin Rotan dance accompaniment. The purpose of this study was to describe the analysis of musical accompaniment of Jepin Rotan dance in Pontianak. The theory used was about the structure of music, elements of music, musicology, rhythmic patterns, musical forms and chords. The method used in this research was analytic descriptive method with qualitative research form. The approach used in this research was the musicology approach. Data obtained from interviews and observations about the accompaniment of Jepin Rotan dance in Pontianak. Data collection tools used in this study were researcher as the main instrument, interview guidelines and observation guidelines. Checking the validity of the data of this study was used the extension of observation and triangulation techniques. Data analysis techniques in this study were data reduction, data presentation, and drawing conclusions. The results of this study indicated that Jepin Rotan dance accompaniment was a musical composition with one part and has two sentences. The tempo used was between 90 and 120. In the vocals there was also some ornaments or twists on the accompaniment song of the Jepin Rotan dance. Jepin Rotan dance accompaniment had a form that included two sentences, two phrases and two motifs. Based on the results of this study are expected to reactivate traditional artists, especially those in the Pontianak, West Kalimantan.Â Key words: Analysis, Music Accompanied of Jepin Rotan